PENGARUH KARAKTERISTIK PEKERJAAN, KOMUNIKASI INTERNAL DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA PADA PT. CITRA CITI PACIFIC PEKANBARU (STUDI PADA PENGELOLA MALL SKA PEKANBARU) - Lubis, Suryana Tessa; Sasmita, Jumiati; Rama, Rovanita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine the effect of job characteristics, internal communications, and transformational leadership on employee job satisfaction at PT. Citraciti Pacific Pekanbaru. The population in this study were all employees at PT. Citraciti Pacific Pekanbaru totaling 98. While the sampling technique using census method. Analysis of data using multiple linear regression with SPSS program. Based on the results of data analysis known that the job characteristics, internal communications, and the simultaneous effect of transformational leadership on employee job satisfaction at PT. Citraciti Pacific Pekanbaru, job characteristics partial effect on employee job satisfaction, internal communication partial effect on employee job satisfaction, leadership transformational partial effect on employee job satisfaction. So to maximize employee satisfaction, the company should give a salary appropriate and balanced with the workload on the responsibility of employees, to maximize the characteristics of the job, workers will always contribute to the resolution of existing problems in the company, to maximize internal communications, expected leaders improve surveillance systems No order to work properly, and to maximize the transformational leadership, it is expected the company to provide sanctions for employees or leaders who do not arrive on time, especially when there are meetings and so forth.Keywords: Job Characteristics, Communication, Leadership, and Satisfaction.